Efektivitas Penggunaan Media Sosial terhadap Pemasaran Perumahan pada PT Borneo Real Properti (Studi Kasus PT Borneo Real Properti Kota Baru Pontianak) - Nugroho, Nugroho; Firayanti, Yuni; Syaifudin, Syarif Muhammad (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
PT. Borneo Real Properti is a part of the PT Fachri Property Group, part of the largest property developer in West Kalimantan which operates in the property sector (Real Estate). ). This company was founded on June 7 2018, founded by Mr. Mochammad Fachri S, Sos. PT Borneo Real Properti utilizes social media in marketing housing. The efforts made are by carrying out promotions on several social media such as Facebook, Instagram, WhatsApp, YouTube and Tiktok. In this research, data was obtained through informants. The informants in this research are consumers, potential consumers, marketing staff, and HRD managers. This research aims to determine the effectiveness of social media on housing marketing at PT Borneo Real Properti. This research is qualitative research. Data collection through interviews, observation and documentation. Analyze this research data using qualitative data analysis. Based on the research results, it can be concluded that social media is effective in marketing housing as seen from the fact that after using social media PT Borneo Real Properti's consumers increase every month and housing sales increase every year. Barriers to marketing housing via social media are expensive advertising costs and competition between property companies with interesting content on social media.